A method of producing compreg oil palm wood - Bakar, Edi Suhaimi; Ashaari, Zaidon; Choo, Adrian Cheng Yong; Abare, Alhassan Yakubu (2014)
The present invention relates to a method of producing compreg oil palm wood comprising the steps of obtaining an oil palm log from an oil palm tree, debarking the oil palm log, cutting the oil palm log into a slab, edging the slab, compressing the slab to reduce moisture content in the slab, drying the slab to further reduce the moisture content in the slab, introducing the slab with resins, semi-curing the slab by heating, and compressing the slab to form compreg oil palm wood, characterized in that the slab is steamed prior to the compression of the slab to control the extent of micro-cracking in the slab in which the control of the micro-cracking in the slab facilitates the steps of drying and introduction of resins.